Technological route and characteristics of home - built Ag, Ag/Cu, and Ag/Ni ohmic conductor pastes - Khalaf, Mohammed K. (Iraqi Journal of Physics, 2011)
The current research reports the preparation and fabrication of the silver paste conductor which is employed as a soldering material for electro – optical components ohmic interconnections. The prepared paste possesses electrical characteristics identical to the ohmic connectors as its observable from resistance – temperature variation. Moreover, the I – V characteristics obeys Ohm’s law and this dependency was further confirmed by the nearly constant capacitance measurements with voltage and frequency. A noticeable improvement in electrical conductivity, compared to the pure silver paste sample, was noted for samples prepared by mixing predetermined weight ratios of brass and copper. Furthermore, stability of electrical resistance with time was investigated and the resistance was approximately constant